2020
DOI: 10.1007/s11096-020-01078-1
|View full text |Cite
|
Sign up to set email alerts
|

Provision of community pharmacy services during COVID-19 pandemic: a cross sectional study of community pharmacists’ experiences with preventative measures and sources of information

Abstract: Background An infectious disease caused by a novel coronavirus (later called COVID-19) reached pandemic levels in 2020 and community pharmacists were involved in responding to this pandemic, also in Kosovo. Objectives To explore the experiences of community pharmacists in relation to provision of community pharmacy services during COVID-19 pandemic. Setting Community pharmacists in Kosovo. Methods This was a cross-sectional study where data was collected via a selfadministered online questionnaire, from 264 ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
3
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 16 publications
7
90
3
9
Order By: Relevance
“…A previous study in Kosovo involving community pharmacists reported that implementation of preventative measures was associated with respondents’ perception that pharmacists and the pharmacy profession were valued more by patients and other health professionals. 23 However, pharmacies received no external funding support to adopt such preventative measures, similar to the experiences faced by our study participants. Key barriers to pharmacy activities included the requirements to restructure the physical environment to ensure social distancing.…”
Section: Discussionmentioning
confidence: 83%
“…A previous study in Kosovo involving community pharmacists reported that implementation of preventative measures was associated with respondents’ perception that pharmacists and the pharmacy profession were valued more by patients and other health professionals. 23 However, pharmacies received no external funding support to adopt such preventative measures, similar to the experiences faced by our study participants. Key barriers to pharmacy activities included the requirements to restructure the physical environment to ensure social distancing.…”
Section: Discussionmentioning
confidence: 83%
“…According to a cross-sectional study carried out by Hoti and colleagues [ 38 ], slightly less than 90% of community pharmacists have a sufficient and adequate knowledge of COVID-19-related preventative measures and correctly implement them. Most pharmacists utilize mobile devices to access COVID-19 related information and actively counteract the dissemination of misleading information concerning COVID-19.…”
Section: The Role Of Hospital and Community Pharmacists During Thementioning
confidence: 99%
“…25 In a study employing the transtheoretical model of change, Hoti et al found pharmacists to outweigh pros versus cons and be in high levels of readiness to engage in risk mitigation strategies related to COVID-19. 26 …”
Section: What Have We Done So Far?mentioning
confidence: 99%